Usage Effectiveness Analysis Direct Shopping Budget on Budget Based Performance at the District Office Helvetia Field - Evi Apriani; Mika Debora; Puja Riqki Ramadhan (Budapest International Research and Critics University, 2022)
This study aims to determine the effectiveness of the use of direct budgets in performance-based budgeting. The data taken in this study is an overview, at the district office of Medan Helvetia organizational structure and reports on the realization of regional revenue and expenditure budgets. Data collection techniques used are observation and interviews. The types of data used are qualitative and quantitative data. Sources of data used are primary data and secondary data. Data analysis using descriptive analysis techniques, namely collecting data according to the truth then the data is compiled, processed, and analyzed to provide an overview of existing problems, and the analysis of the realized effectiveness ratio is divided by the budget target multiplied by 100%. The results of the study show the effectiveness of using the 2021 direct expenditure budget for a performance-based budget of Rp. 8,783,038,738 or 80.77%, so that there is a budget difference of Rp.2,091,252,962. 77%. The effectiveness of the use of the direct expenditure budget on the performance-based budget in 2021 is Rp. 10,096,190,641 or 83.38%. So that there is a difference in the budget deficit of Rp. 2,013,072,359. The level of budget effectiveness criteria used in 2021 is only quite effective because the presentation of its achievements is 83.38%. 641 or 83.38%. So that there is a difference in the budget deficit of Rp. 2,013,072,359. The level of budget effectiveness criteria used in 2021 is only quite effective because the presentation of its achievements is 83.38%. 641 or 83.38%. So that there is a difference in the budget deficit of Rp. 2,013,072,359. The level of budget effectiveness criteria used in 2021 is only quite effective because the presentation of its achievements is 83.38%.